The Factors Influencing Innovative Work Behavior (IWB) Among Employees at Malaysia Airport Holding Berhad, Terminal Service Division, Kuala Lumpur International Airport, Malaysia - Rusli, Nurul Aida Natasha; Zaman, Maliza Delima Kamarul (Advances in Social Sciences Research Journal, 2024)
Innovative work behaviour (IWB) among employees has parallel increase in priority for employees that have concern in quality of work and to increase employees’ satisfaction. It is not anymore, a new thing to a working world. Thus, this research analysed the factors affecting employees’ innovative work behaviour at Malaysia Airport Holdings Berhad. The research examined the relationship between transformational leadership, person-organizational fit, perceived organizational support, psychological well-being, as well as interpersonal conflict and IWB. Therefore, a framework and six hypotheses were developed. A total of 74 respondents of Malaysia Airport Holdings Berhad (MAHB), Terminal Service Division (TSD), Kuala Lumpur International Airport participated in this study which was conducted through online Google Form. Quantitative research was conducted using cross-sectional method by distributing verified questionnaire. The data obtained for this study was analysed with Statistical Package for Social Science (Version 28.0). The findings indicated that transformational leadership, person-organizational fit, perceived organizational support, and psychological well-being had significant impacts on IWB. However, there was no relationship between interpersonal conflict and innovative work behaviour. It was also analysed that the most significant factor was Person-organization fit. Therefore, the organization and employees of Malaysia Airport Holdings Berhad, Terminal Service Division (TSD), Kuala Lumpur International Airport were hoped to concentrate on Person-organizational fit to enhance innovative work behaviour thus improve performance.